Knocking on tax haven's door: Multinational firms and transfer pricing - Ronald B. Davies; Julien Martin; Mathieu Parenti; Farid Toubal (University College Dublin, UCD School of Economics, 2014)
This paper analyzes the transfer pricing of multinational firms. We propose a simple framework in which intra-firm prices may systematically deviate from arm's length prices for two motives: i) pricing to market, and ii) tax avoidance. Multinational firms may decide not to avoid taxes if the risk to be sanctioned is high compared to the tax gap. Using detailed French firm-level data on arm's length and intra-firm export prices, we find that both mechanisms are at work. The sensitivity of intra-firm prices to foreign taxes is reinforced once we control for pricing-to-market determinants. Most importantly, we find almost no evidence of tax avoidance if we disregard exports to tax havens. Back-of-the-envelope calculations suggest that tax avoidance through transfer pricing amounts to about 1% of the total corporate taxes collected by tax authorities in France. The lion's share of this loss is driven by the exports of 450 firms to ten tax havens. As such, it may be possible to achieve significant revenue increases with minimal cost by targeting enforcement.
Keywords: F23; H25; H25; H32; 330; Transfer pricing; Tax haven; Pricing to market